Malay reservation land: a mere title or protection of the Malay rights? / llyani Alias and Nor Asyikin Zakaria - Alias, llyani; Zakaria, Nor Asyikin (2006)
This Honours Project Paper entitled Malay Reservation Land: A Mere Title or Protection of Malay Rights?, was chosen by us due to the fact that this issue is quite sensitive and it need clarification on the purpose of the Malay Reservation itself. The term Malay itself has many definitions and this is confusing. As we can see today, the number of Malay Reservation is decreasing even though there are restrictions imposed upon the owner of the Malay Reservation in matter of dealings. Why is this happening? What is the main purpose of having the Malay Reservation in Malaysia? Is it a mere title which means nothing or is it a protection of Malay rights and privileges to ensure the Malay did not become wanderers in their own land? That is for us to discover as the outcome of our Honours Project Paper.